Phishing Awareness and Susceptibility of System Users - R. Senkathir, Dr.; Bushan D. Sudhakar, Dr. (International Journal of Engineering and Technology, 2018)
The significant rise in the occurrences of phishing events or attacks is very disturbance from the society view point as it extends varied sects of people each year. With an enormous amount of money lost to online crimes, security on the web becomes increasingly important. Security experts need to understand the ways by which individual’s interaction with phishing attacks and their way of behavior. There is a need for a deeper understanding of people Attitude, Intentions, Behavior, in order to protect them from falling into the clutches of the cybercriminals. This research work has attempted in order to understand potential risks of information security posed by computer system users as they are the weakest link in the information security range of defense. The study examines the awareness of users to decrease the risk of e-mail phishing by studying the awareness of phishing among Computer System users.